Archaeology and archaeometallurgy: some unresolved areas in the interpretation of analytical data - Pearce, Mark (Taylor & Francis, 2016)
This paper uses examples from Mediterranean and in particular Italian prehistory to explore the interface between prehistoric archaeology and metals analysis by examining three areas: the usefulness of data from past analyses (‘what is it made of?’), lead isotope analysis and the problem of unpublished data (‘where is it from?’), and the interpretation of analytical data (‘what does it mean?’). Issues discussed include big data, the integration of datasets from different analytical programmes (especially where analytical results are in disagreement), and open access and the withholding of data through incomplete publication, which means that conclusions cannot be verified. It offers some suggestions as to how communication between archaeologists and archaeometallurgists can be improved.